Pertumbuhan dan Hasil Baby Kailan (Brassica Oleraceae Var. Acephala) Kultivar New Veg Gin Dengan Waktu Aktivasi Aerator dan Perbedaan Nilai Ec pada Sistem Hidroponik Rakit Apung (Floating Raft) - Anna Rofiyana; Rommy Andhika Laksono; Bastaman Syah (Peneliti.net, 2021)
One methods that can be used for cultivate baby kailan on limited land is the planting technique of floating rafts hydroponic system. The experiment was conducted in a screen house, Cianting district, Purwakarta Regency from July to August 2021. The research method was used experimental method with Randomized Block Desain (RBD) Factorial cconsisting of 9 treatments 3 replications. The first factor was aerator ativation time consisting of 3 levels, namely a1 (24 hours), a2 (12 hours with interval “on/off” 30 minutes ), and a3 (without aeration). The second factor is the EC of 3 levels, namely e1 (e1 (1,5 – 2,0 mScm-1), e2 (2,0 – 2,5 mScm-1), and e3 (2,5 – 3,0 mScm-1). The effect of threatment in the analysis with variety analysis and if the F test level is 5% significant, then to know the best treatment continued with dmrt test (Duncan Multiple Range Test) at the level of 5%. The result showed that there was no interaction between the aerator and EC value difference on each parameter baby kailan. Threatment of aerator activation time 24 hours can produe the highest average fresh weight 30,08 gram. Threatment EC value 1,5 – 2,0 mScm-1 gives average of highest fresh weight baby kailan 25,51 gram.